MATERIAL SOURCES OF CONTEMPORARY CIVIL LAW - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Not much attention has been given to material sources of civil law, in newer legal literature. It is evident that we are missing deeper researches which would contribute to the development of legal science, as well as the legal regulative in that field. It would definitively show that simplified, student book presentation of material sources is insufficient and outdated since long ago. Today, a lot of factors influence forming of civil law, such as: human needs, available resources, social relationships, legal tradition, value system, level of economic development, involvement in integration processes, legal politics, etc. It is indeed a very complex and important issue, which demands cooperation between experts in different fields. The author also points out the need for working on development of anthropology, sociology, philosophy, ethics, economy and politics of civil law, as separate scientific disciplines.